“I don’t care about the money”: A thematic analysis of parenting practices of youth sport - Caly Setiawan (Lambung Mangkurat University, 2022)
Abstract The purpose of this study was to investigate practices of raising up young athletes from a sociological perspective. In particular, I looked at how parents enacted their capitals within the contexts of youth sport as a social field. This qualitative study involved 6 participants who had experiences of parenting their children in youth sport for at least five years. Data were collected through in-depth interviews. Thematic analysis was employed to facilitate inductive analysis toward the construction of themes from the data. A computer assisted qualitative data analysis software (CAQDAS), namely ATLAS.ti 22, was utilized to help the researcher manage complex data set and achieve trustworthiness criteria. Three themes have been constructed through mainly inductive analysis. These were (1) the contextual practices of youth sport as social field, (2) economic, cultural and social capital at play in parenting practices of youth sport, and (3) capital exchange as practices within and beyond youth sport. The current study concludes that sociological thoughts on social field and capitals are advantageous to understand the social complexity of day-to-day parenting practices of youth sport. However, agenda for further studies would need to explore the field of youth sport utilizing other sociological frameworks.